Frequency of Opium Addiction with Ischemic Stroke Patients and Comparing Their Cerebrovascular Doppler Ultrasound Alternations to Non-Addicts - Akbar Hamzei-Moghaddam; Mohammad Ali Shafa; Narges Khanjani; Reza Farahat (Addiction and Health, 2013)
Background: Ischemic stroke is a major cause of mortality and morbidity worldwide. Various studies on the etiology of this disease are in progress. Some studies have suggested that opium abuse may is associated with increased risk of ischemic stroke. The present study aimed to analyze the frequency of opium addiction and to compare cerebrovascular ultrasound patients’ changes to non-addicts. Methods: This cross-sectional study was performed on 97 patients with ischemic stroke. The diagnosis was confirmed by imaging and paraclinical studies. All the patients underwent cerebrovascular ultrasound in the first 4 days of symptoms onset. A questionnaire containing demographic data, opium use information [based on the 4th Edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) criteria], and vascular ultrasound findings were completed for each patient and the results were analyzed using descriptive statistics and chi-square test. Findings: In this study, 38 patients (39.18%) were addicted to opium and the remaining were non-addicts. Among the addicted patients, 31 patients were male and 7 patients were female, while 26 and 33 patients of non-addicts were male and female, respectively (P < 0.01). Among the risk factors for stroke, smoking was higher in the addicts than in non-addicts (P = 0.04). Frequency of vascular stenosis and stenosis location did not show a statistical significant difference between the addicted and non-addicted patients. Conclusion: More than one-third of the patients with stroke were addicted to opium which was higher than general population; although the pattern of stenosis in these patients was similar to the non-addicts. Keywords: Opium, Transcranial Doppler Ultrasound, Stroke